2013
DOI: 10.5005/jp-journals-10026-1057
|View full text |Cite
|
Sign up to set email alerts
|

MTA-Based Root Canal Sealers

Abstract: Mineral trioxide aggregate (MTA) has been recommended for pulp capping, pulpotomy, apical barrier formation in teeth with open apexes, repair of root perforation and root canal obturation. Since, its introduction in 1993 by Torabinejad numerous studies have been published regarding various aspects of this material. The aim of this review was to consider MTA as root canal sealer and various laboratory experiments and clinical studies of MTAbased root canal sealers. An extensive search of the endodontic literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…When observed under X-ray diffraction and SEM analysis, this adherent interstitial layer is indistinguishable from hydroxylapatite in composition and structure. 4 The physical properties of epoxy resin-based sealers are appreciable and also have a very good apical sealing ensuring adequate biological performance, but it has several disadvantages in clinical use, radiopacity, and retreat ability. Thus, there remains no perfect adhesive material designed solely for endodontic purposes and becomes important to develop one which is suitable to use in such procedures.…”
Section: Jcdpmentioning
confidence: 99%
“…When observed under X-ray diffraction and SEM analysis, this adherent interstitial layer is indistinguishable from hydroxylapatite in composition and structure. 4 The physical properties of epoxy resin-based sealers are appreciable and also have a very good apical sealing ensuring adequate biological performance, but it has several disadvantages in clinical use, radiopacity, and retreat ability. Thus, there remains no perfect adhesive material designed solely for endodontic purposes and becomes important to develop one which is suitable to use in such procedures.…”
Section: Jcdpmentioning
confidence: 99%
“…However, several studies have shown that some of these materials may cause cellular degeneration and delayed wound healing of periapical tissues [29, 30]. The cytotoxic effect of these endodontic sealers may be caused by heavy metals released from the set materials [11, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…This layer hermetically seals the root canal, thereby eliminating remaining microbes. The MTA sealer is composed of calcium oxide which, every time it contacts water, creates Ca(OH) 2 that breaks into calcium and hydroxyl ions, thereby maintaining a high pH in the tissue [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium hydroxide (Ca(OH) 2 ) sealer, which is biocompatible, has limited antimicrobial activity [4,5]. The mineral trioxide aggregate (MTA) sealer has good adhesion, hydrophilic, biocompatibility, and antimicrobial properties [6].…”
Section: Introductionmentioning
confidence: 99%